SEXUALIDADE NA TERCEIRA IDADE: MEDIDAS DE PREVENÇÃO PARA DOENÇAS SEXUALMENTE TRANSMISSÍVEIS (REMUNOM, 2024)
For sexually transmitted diseases. It aims to analyze and understand what measures should be taken to prevent sexually transmitted diseases in old age. In this context, the justification for this study is focused on the importance of bringing up discussions about STIs in old age, since this topic has great relevance both in academic training and in the field of professional development. From this perspective, the following question is presented as the main problem: What factors promote the vulnerability of elderly people to STIs? And what is the role of the nursing professional in intervening in reducing these cases? The research methodology used is bibliographic, which made it possible This article discusses the importance of sexuality in old age and prevention measures to identify the main points of view of studies relating to sexuality in old age. Thus, the results of this study demonstrate that it is essential for health professionals, especially nurses, to understand and consider sexuality in the care of the elderly, promoting a comprehensive approach that takes into account the importance of emotional and physical balance at this stage of life. The conclusion reached through this research is that there is a positive correlation between healthcare professionals in preventing STIs in old age. Keywords: Elderly, Aging, Health of the Elderly; Sexually Transmitted Infections.